Teaching zoology in basic education in Brazil: an analysis of bibliographic publications (2010-2020) - Jailma Ferreira da Silva; Jéssica Prata; Martin Lindsey Christoffersen (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2021)
The teaching of zoology, although recent in basic education, is questioned methodologically. The main criticisms are that zoology teaching still follows an Aristotelian essentialist view. It is based on traditional expositions in the classroom, and it fragments and decontextualizes contents. All this hinders learning, especially when we are dealing with such a complex area with a wide variety of names and concepts. Thus, through bibliographic research, we seek to identify, analyze, and describe some study trends in Brazil, during the period 2010-2020. We also verify the challenges involved in attaining improvement in pedagogical practices. A total of 197 articles, 32 dissertations, and one thesis were identified. The following descriptors were used: a) type of production; b) temporal distribution; c) geographic distribution; d) institution of origin of the publications; e) levels of education; f) thematic focus; g) type of research. With this, it was possible to describe the main aspects related to the teaching of zoology in basic education in Brazil, providing an insight into the direction of academic productions towards this theme, thus serving as a basis for other investigations